2002
DOI: 10.1071/sr01046
|View full text |Cite
|
Sign up to set email alerts
|

Soil clay–humus complexes. II. Bridging cations and DTA studies

Abstract: Clay-humus complexes, isolated from 5 soils (Entisol, Alfisol, Vertisol, two Mollisols), were extracted with 0.1 n citrate, EDTA, and oxalate at pH 7.0-10.0; amounts of Ca2+, Mg2+, Fe3+/2+, Al3+, as well as humic acid (HA) in the extract were determined. HA extracted increased with pH and varied with nature of ligand; largest amounts were extracted by EDTA at high pH. In the Entisol clay-humus extract, Ca2+ is dominant. In Alfisol sample, Ca2+ and Mg2+ have little role in clay-HA bonding; apart from monovalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The results provide some evidence to support the idea that the measured Q value was possibly attributable to oxidative reactions of OC, especially the oxidation of aromatic C. Additionally, Q oc was positively related to ash content (r = 0.63, p b 0.01; Fig. S6b), which was probably due to the fact that minerals can increase the molecular strain in SOM and thus promote its thermal decomposition of SOM (Ahmed et al, 2002). The thermal stability of the samples varied greatly, as indicated by 50% T and PT values ( Table 1).…”
Section: Characteristics Of Som Fractionssupporting
confidence: 61%
“…The results provide some evidence to support the idea that the measured Q value was possibly attributable to oxidative reactions of OC, especially the oxidation of aromatic C. Additionally, Q oc was positively related to ash content (r = 0.63, p b 0.01; Fig. S6b), which was probably due to the fact that minerals can increase the molecular strain in SOM and thus promote its thermal decomposition of SOM (Ahmed et al, 2002). The thermal stability of the samples varied greatly, as indicated by 50% T and PT values ( Table 1).…”
Section: Characteristics Of Som Fractionssupporting
confidence: 61%
“…Chelating agents are known to mobilize OM (Yang et al, 2001), which is explained by the disruption of cation bridges between individual molecules. Further, the stability of organo-mineral associations has been explained with the formation of cation bridges between clay mineral and OM (e.g., Ahmed et al, 2002;Fischer and Buttchereit, 2002;Yang et al, 2001).…”
Section: Molecular Aggregation and Supramolecular Structurementioning
confidence: 99%
“…Thermal analyses have also been used to elucidate the nature and degree of association of organic matter with mineral surfaces: while Lutwick (1972) found no differences in the DTG traces of clay-organic matter complexes versus alkali-extracted organic matter, Schulten and Leinweber (1999) demonstrated higher peak temperatures in the heavy fraction of a soil (N2 g cm À3 ) compared to the light fraction and attributed this to chemical bonding to mineral surfaces. Using differential thermal analysis (DTA), Ahmed et al (2002) found that clay-humus complexes had lower thermal decomposition temperatures than extracted humic acids, which they attributed to aromatic ring strain caused by adsorption to the clay surfaces. Thermal techniques have also been used to quantify black carbon (BC), an aromatic and condensed fraction of organic matter derived from the incomplete combustion of plant material or fossil fuels.…”
Section: Introductionmentioning
confidence: 99%